The Role of Adipokines in Pancreatic Cancer - Wang, Qi; Wang, Huizhi; Ding, Yuntao; Wan, Mengtian; Xu, Min (Frontiers in Oncology, 2022)
In modern society, inappropriate diets and other lifestyle habits have made obesity an increasingly prominent health problem. Pancreatic cancer (PC), a kind of highly aggressive malignant tumor, is known as a silent assassin and is the seventh leading cause of cancer death worldwide, pushing modern medicine beyond help. Adipokines are coming into notice because of the role of the intermediate regulatory junctions between obesity and malignancy. This review summarizes the current evidence for the relationship between highly concerning adipokines and the pathogenesis of PC. Not only are classical adipokines such as leptin and adiponectin included, but they also cover the recognized chemerin and osteopontin. Through a summary of the biological functions of these adipokines as well as their receptors, it was discovered that in addition to their basic function of stimulating the biological activity of tumors, more studies confirm that adipokines intervene in the progression of PC from the viewpoint of tumor metabolism, immune escape, and reprogramming of the tumor microenvironment (TME). Besides endocrine function, the impact of white adipose tissue (WAT)-induced chronic inflammation on PC is briefly discussed. Furthermore, the potential implication of the acknowledged endocrine behavior of brown adipose tissue (BAT) in relation to carcinogenesis is also explored. No matter the broad spectrum of obesity and the poor prognosis of PC, supplemental research is needed to unravel the detailed network of adipokines associated with PC. Exploiting profound therapeutic strategies that target adipokines and their receptors may go some way to improving the current worrying prognosis of PC patients.